EVALUASI PELAKSANAAN RUJUKAN IBU BERSALIN PENGGUNA KARTU SEHAT OLEH BIDAN DI RUMAH SAKIT UMUM - Sulastri, Eis (Universitas Jenderal Achmad Yani Yogyakarta, 2012)
Background: Maternal referral is conducted with the aim of providing better care for patients; however, it also presents risks, especially inapatient’s critical condition since it can increase maternal morbidity andmortality. It is important to carry out the referrals guidelines according to the standards for midwives, that is, BAKSOKU standards. In the Profile of Central Lombok District Health Office, there are as many as 21,357 pregnant women. Yet, there are 8,800 pregnant women who have a health card (health insurancefor the poor) in which, of the number mentioned, 1,157 pregnant women have been referred to Praya District Hospital using the health card. In particular, the maternity room has served as many as 1,260 deliveries, 818 of which were referral cases by the midwife and 715 (87.4%) of 818 patients were referralcases using the health card. Objective:To find out the maternal referral implementation for health card users by midwives at Praya Local Hospital of Central Lombok District. Methods: This was an evaluation study with a cross-sectional design. The sampling technique was with consecutive sampling. Samples were maternal health card users referred to the Maternity Room at Praya Local Hospital as many as 70. In this study, an evaluation was carried out to the aspects of input,process, and output. Quantitative data analysis used Univariable analysis, Bivariabel analysis with Chi-square statistical test, and Multivariable analysis with logistic regression statistical test. Results:The input variable of high-risk maternal referral had a significant relationship with the BAKSOKUstandards suitability on the value of p <0.009 and the value of RP = 3.35, CI95% = 1.18 to 9.50. Otherinput variables that had a relationship with the BAKSOKU standards were midwives’ education, NormalMaternity Care training and years of service. Conclusion: The process of maternal referral in accordance with the BAKSOKU standard was still low. The factors of maternal condition, Normal Maternity Care training, education and years of service were related to the implementation ofthe BAKSOKU standards Keywords: Evaluation,referralsystem, standard